Caracterización de los desechos sólidos y propuestas para el aprovechamiento en las parroquias rurales Moromoro y Palosolo - Muñoz Galvez, Arlet Melissa; Mendoza Suncion, Ruth Melissa (Machala : Universidad Técnica de Machala, 2025)
The general objective of the research was to characterize the solid waste generated in the rural parish of Moromoro to formulate proposals for its utilization that contribute to comprehensive and sustainable waste management and minimize its environmental impact. The methodology used was based on an approach suggested by the Pan American Center for Sanitary Engineering and Environmental Sciences (CEPIS). A field study was carried out with a representative sampling in four zones: Moromoro Parish, El Cacao neighborhood, La Providencia neighborhood, and the Palosolo population center. Parameters such as per capita generation, composition, and density of solid waste were calculated. The results showed that the La Providencia neighborhood generated the largest amount of solid waste (1109.37 kg), while the El Cacao neighborhood generated the smallest amount (482 kg) during the sampling week. The total waste generated in the entire parish was 3273.85 kg during that week. The document emphasizes the need for comprehensive strategies that include environmental education, adequate funding, improved infrastructure, and active community participation. Finally, various utilization initiatives are proposed, such as collective collaboration between the Municipal GAD of Piñas, the Parochial GAD of Moromoro, and the population, for more efficient and co-responsible waste management.
El objetivo general de la investigación fue caracterizar los desechos sólidos generados en la parroquia rural Moromoro para formular propuestas de aprovechamiento que contribuyan a una gestión integral y sostenible de los residuos y minimicen su impacto ambiental. La metodología utilizada se basó en un enfoque sugerido por el Centro Panamericano de Ingeniería Sanitaria y Ciencias del Ambiente (CEPIS). Se llevó a cabo un estudio de campo con un muestreo representativo en cuatro zonas: Parroquia de Moromoro, Barrio El Cacao, Barrio La Providencia y el Centro poblado Palosolo. Se calcularon parámetros como la generación per cápita, la composición y la densidad de los residuos sólidos. Los resultados mostraron que el Barrio La Providencia generó la mayor cantidad de residuos sólidos (1109,37 kg), mientras que el Barrio El Cacao generó la menor cantidad (482 kg) durante la semana de muestreo. El total de residuos generados en toda la parroquia fue de 3273,85 kg en esa semana. El documento enfatiza la necesidad de estrategias integrales que incluyan educación ambiental, financiamiento adecuado, mejor infraestructura y la participación activa de la comunidad. Finalmente, se proponen diversas iniciativas de aprovechamiento, como la vinculación colectiva entre el GAD Municipal de Piñas, el GAD parroquial de Moromoro y la población, para una gestión de residuos más eficiente y corresponsable.
Keywords: RESIDUOS SOLIDOS; GESTIÓN INTEGRAL DE RESIDUOS; CARACTERIZACIÓN DE DESECHOS; APROVECHAMIENTO DE RESIDUOS